Design studies of a proof-of-principle experiment on THz SASE FEL at PITZ. (November 2019) - Li, X.-K.; Krasilnikov, M.; Boonpornprasert, P.; Shaker, H.; Chen, Y.; Good, J.; Gross, M.; Huck, H.; Isaev, I.; Koschitzki, C.; Lal, S.; Lishilin, O.; et al.
Abstract: A free-electron laser based THz source is undergoing design studies at the Photo Injector Test facility at DESY in Zeuthen (PITZ). It is considered as a prototype for pump-probe experiments at the European XFEL, benefiting from the fact that the electron beam from the PITZ facility has an identical pulse train structure as the XFEL pulses. In the proposed proof-of-principle experiment, the electron beam (up to 4 nC bunch charge and 200 A peak current) will be accelerated to 16-22 MeV/c to generate SASE radiations in an LCLS-I undulator in the THz range between 60 and 100 pm with an expected energy of up to ~1 mJ/pulse. In this paper, we report our simulations on the optimization of the photo-injector and the design of the transport and matching beamline. Experimental investigations on the generation, characterization and matching of the high charge beam in the existing 22-m-long beamline will also be presented.